Identification of Mangrove Plants with Medicinal Potential in Muara Kintap Village Tanah Laut Regency - Safitri, Adinda Ayu; Putra, Guruh Mayka; Rizali, Akhmad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Indonesia has the largest mangrove area in the world with high biodiversity potential, including in Muara Kintap Village, Tanah Laut Regency. Mangroves function not only ecologically but also hold medical potential as raw materials for biopharmaceuticals due to their bioactive compound content. This research aims to identify and document mangrove species with potential as herbal medicine ingredients in the mangrove ecosystem of Muara Kintap Village. The study was conducted in September 2025 using purposive observation and the cruising method for primary data collection, supplemented by a systematic literature review for secondary data. The results identified five major species with medicinal potential: Avicennia marina, Sonneratia alba, Avicennia officinalis, Rhizophora apiculata, and Nypa fruticans. The leaves are the most dominant organ with pharmacological potential across all identified species. Secondary metabolite compounds found include flavonoids, tannins, saponins, steroids, and terpenoids, which function as antibacterial, antioxidant, anti-inflammatory, and anticancer agents. This documentation is expected to serve as a foundation for developing herbal-based health products while supporting mangrove conservation efforts in coastal areas.